Aplikasi Pencarian Showroom Yamaha di Kota Tasikmalaya Berbasis Android Menggunakan Metode Location-Based Service (LBS) dan Framework React Native (Journal Digital Technology Trend, 2022)
The Yamaha Showroom is a place for repairing and selling spear parts. Not all Yamaha showroom locations can be known by the public, both those from the City of Tasikmalaya and those from outside the city. This is due to a lack of information about the Yamaha showroom in Tasikmalaya City. This study aims to build an android-based Yamaha showroom search application as a source of information to find out the location and route to the showroom location in Tasikmalaya City. The application design method involves modeling using UML (Unified Modeling Language) and location-based service (LBS) applied to the Yamaha showroom search application that was built. The results of the research resulted in a Yamaha showroom search application in Tasikmalaya City that can help the community in finding Yamaha showroom locations in Tasikmalaya City. This showroom search application in the city of Tasikmalaya can help show the direction to go. This application provides information about the opening hours and location of the Yamaha showroom. The LBS method applied to this application is for coordinate points that are more accurate and can be used anywhere and anytime by the public and easy to use.